2021
DOI: 10.1088/1755-1315/901/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Scientific And Economic Justification Of Application Of Symbiotic Polycomponent Fodder Additive In Feeding High Productive Cows

Abstract: Research has been carried out on the use of the symbiotic “Rumimaster” in balanced diets of highly productive cows in the conditions of the breeding plant “Kirovskaya meadow-bog experimental station”. The experiment was carried out on two groups of animals in the middle of lactation with a duration of 90 days. The inclusion of the feed additive “Rumimaster” in the diet of experienced cows contributed to an increase in the gross production of natural and 4% fat milk by 124.5 kg and 128.4 kg, the yield of milk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Multicomponent synbiotics contain both probiotics and prebiotics in addition to enzymes. Usage of synbiotics helps increase the digestibility of structural carbohydrates, cow productivity, and milk quality and optimizes the body's metabolic processes ( 4 , 7 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multicomponent synbiotics contain both probiotics and prebiotics in addition to enzymes. Usage of synbiotics helps increase the digestibility of structural carbohydrates, cow productivity, and milk quality and optimizes the body's metabolic processes ( 4 , 7 , 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the use of multicomponent feed additives based on probiotic cultures containing Bacillus subtilis and Bacillus licheniformis , which regulate the rumen microbial synthesis and allow reducing the adverse effects of evolving digestive system diseases of young and adult animals, as well as the consequences of feeding low-quality feed, is practiced worldwide ( 4 , 5 , 13 ). Moreover, the inclusion of feed additives of pro- and prebiotic action (synbiotics) contributes to increasing the productivity of cows, improving the quality of milk, and the intensity of rumen digestion ( 16 , 17 ) had shown that, the use of B. subtilis and B. licheniformis , complex enzymes, and probiotic cultures positively affects animal productivity and stimulates the fermentation of nutrients in the rumen of highly productive dairy cows.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the microorganisms of cow rumen play a primary role in the processes of digestion; meanwhile, it is necessary to emphasize that their functional significance is much broader. The symbiotic microflora of the rumen perform a detoxification function, participate in the digestibility of nutrients, prevent the invasion of parasites and pathogens and stimulate the development of immunity [ 4 , 5 , 6 ]. Therefore, the maintenance and functioning of the microbiota are also important factors in the prevention of gastrointestinal diseases, such as lactate acidosis, alkalosis, ketoses, laminates, mastitis and limb diseases, which significantly increase the productivity of dairy cattle [ 2 , 3 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the process of the growth and development of ruminants and certain anaerobic microorganisms, which develop when feed and water are consumed, symbiotic associations are developed in the rumen. The developed symbiotic relationship between the host and the microbiota results in mutually beneficial cooperation [ 6 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%